Rapid ecological assessment Kerinci Seblat National Park buffer zone: report on plant ecology. - Gillison, A.N.; Liswanti, N.; Rachman, I.A. (1996)
A Rapid Ecological Assessment (REA) was undertaken in two logging concessions bounding the Kerinci Seblat National Park in Central Sumatra. The REA was implemented by WWF Indonesia and funded by the World Bank. CIFOR together with LIPI advised on survey method as part of a wider study involving biodiversity assessment in the Jambi Province. An international team investigated biodiversity pattern in vascular plant species and plant functional groups, insects (mainly butterflies, moths, dung beetles and carabids), herpetofauna (amphibians and reptiles), bats, rodents, large mammals and birds. Unusually restrictive logistics reduced the number of sites to approximately half that needed for a statistical analysis. Results indicate that while plant species and functional richness vary directly with elevation, fauna show a reverse trend. The paper comments on ways of improving logging practices to conserve biodiversity. New global levels of species and functional richness were recorded for several sites. Any future baseline study will require a wider sample of land cover types.